Philosophical Perspectives on Bioethics - Boyle, Joseph M.; Sumner, L. Wayne. (Toronto Studies in Philosophy, 1996)
How should we attempt to resolve concrete bioethical problems? How are we to understand the role of bioethics in the health care system, government, and academe? This collection of original essays raises these and other questions about the nature of bioethics as a discipline. The contributors to the volume discuss various approaches to bioethical thinking and the political and institutional contexts of bioethics, addressing underlying concerns about the purposes of its practice. Included are extended analyses of such important issues as the conduct of clinical trials, euthanasia, justice in health care, the care of children, cosmetic surgery, and reproductive technologies.